A Comparative Overview of High Power Handling CMOS Switches and their Recent Applications in RF Front-Ends - Rascher, Jochen; Zohny, Amr; Glock, Stefan; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (14th Annual Wireless and Microwave Technology Conference (WAMICON), 2013)
In this publication techniques for high power handling capability (PHC) of RF switches in bulk CMOS are investigated and compared. Together with high isolation approaches these allow reconfigurable power amplifiers (PAs) or radio front-ends for Watt level communication standards. Special care is taken to assess the applicability of the solutions for monolithic integration in scaled CMOS processes. Results are shown with PHC as high as 34dBm in a 32nm CMOS process. Recent applications for the switches in front-ends or reconfigurable PAs are analyzed. They show large DC current reduction in back-off with stage bypassing and load adaptation concepts. Up to 50% DC current reduction for low output power is reported. This greatly improves the average PA efficiency for varying envelope signals without the efforts of more advanced solutions like envelope tracking.
elib2cris::1512001600,rascher2013

A Memoryless Semi-Physical Power Amplifier Behavioral Model Based on the Correlation Between AM-AM and AM-PM Distortions - Glock, Stefan; Rascher, Jochen; Sogl, Bernhard; Ußmüller, Thomas; Müller, Jan-Erik; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2015)
A new semi-physical memoryless computationally effective behavioral model (BM) capable of predicting amplitude-modulation-to-amplitude-modulation (AM-AM) and amplitude-modulation-to-phase-modulation (AM-PM) distortions is proposed. In recent years, AM-AM and AM-PM distortions have been separately studied in literature. Here, we investigate the correlation between AM-AM and AM-PM distortions first. Based on the observed correlation, a novel AM-PM model is derived from the well-known Rapp AM-AM model. On the basis of the close relationship between the AM-AM and AM-PM model, a highly accurate and computationally effective large-signal BM is obtained. The newly developed model addresses the current needs of the mobile industry that requires BMs of the power amplifier (PA), which can be interpreted by the designers. In addition, the models must be computationally effective due to the limited computation power in mobile handset. Therefore, only memoryless BMs can be taken into account and larger errors are accepted for the sake of computational effectiveness. In this paper, it is shown that the newly introduced model achieves excellent results, when it is applied to actual industrial applications of two GaAs-based class-AB PAs in 65-nm technology and one CMOS-based class AB PA in 28-nm technology, which are designed for mobile communications.
elib2cris::1512001600,glock2015

An Extension of Power Amplifier Behavioral Models for Optimizing Battery Current at System Level - Glock, Stefan; Sogl, Bernhard; Vizaretta, P.; Ußmüller, Thomas; Müller, Jan-Erik; Fischer, Georg; Weigel, Robert (IEEE Radio and Wireless Week, 2013)
One of the most significant figures of merit concerning a power amplifier is its effficiency. However, behavioral models of power amplifiers are mainly focused on functional aspects but not on current consumption. Therefore, simulations with respect to the efficiency of a power amplifier cannot be accomplished at system level. To close the gap of simulation capabilities, this article proposes a time efficient and accurate extension of behavioral models to predict current consumption. The current consumption model accounts for different bias conditions. For a commercial handset power amplifier, an average error of 1.9% between the fast highlevel model and measurement results is obtained.
elib2cris::1512001600,glock2013

A Novel Power Amplifier Behavioral Model for Improving the Linearity-Efficiency Tradeoff - Glock, Stefan; Rascher, Jochen; Sogl, Bernhard; Ußmüller, Thomas; Müller, Jan-Erik; Fischer, Georg; Weigel, Robert (International Microwave and RF Conference (IMaRC), 2013)
This paper focuses on a novel power amplifier (PA) semi-physical behavioral model (BM) to study the linearityefficiency trade-off in modern wireless transmitter systems. While the behavioral models known in the literature mainly focus on the precise description of the PA nonlinearity in terms of amplitudemodulation- to-amplitude-modulation (AM-AM) and amplitudemodulation- to-phase-modulation (AM-PM) distortions, the model introduced here, also predicts the DC current flowing from the power supply to the PA. This allows to optimize the battery current while keeping the out-of-channel interference within specification limits. In a case study, the DC current and the amplitude distortions of a PA, designed for IEEE 802.11b/g/n applications are predicted with a normalized mean square error (NMSE) of -39.92 dB and -47.07 dB, respectively.
elib2cris::1512001600,glock2013c

A Power-Aware Behavioral Model of a Five-State Phase-Frequency Detector - Glock, Stefan; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (A Power-Aware Behavioral Model of a Five-State Phase-Frequency Detector, 2011)
This paper introduces a power-aware behavioral modeling approach for analog components. A Verilog-A behavioral model, which considers the component’s current consumption, is created using circuit information obtained from transistorlevel simulation. Therefore, the model features high accuracy with the benefit of low computational effort. The concept can be applied to any analog component and enables the simulation of complex analog systems. The approach is practically applied to the design of a phase-frequency detector, which determines important characteristics of a PLL.
elib2cris::1512001600,glock2011a

A Semi-Physical Power Amplifier Behavioral Model Capable of Predicting Gain Expansion Effects - Glock, Stefan; Rascher, Jochen; Sogl, Bernhard; Ußmüller, Thomas; Müller, Jan-Erik; Fischer, Georg; Weigel, Robert (IEEE Topical Conference on RF/Microwave Power Amplifiers for Radio and Wireless Applications, 2014)
A novel semi-physical power amplifier (PA) behavioral model (BM) that describes the input-output characteristic of PAs exhibiting gain expansion (GE) is introduced. The accurate prediction of GE is of particular importance because GE typically improves the power added efficiency (PAE) at high input powers. Though, GE impacts the spectral regrowth. Therefore, BMs that are capable of predicting GE, like the one introduced in this work, are highly desirable. In a case study, the proposed model is employed to predict the AM-AM distortions of a GaAs PA designed for LTE applications. Excellent agreement between measurement and simulation results is obtained. The computational efficient model allows system-level simulations of advanced transmitter systems in order to optimize their modes of operation.
elib2cris::1512001600,glock2014

A state-based power estimation methodology at system level for integrated RF front-ends - Glock, Stefan; Fischer, Georg; Weigel, Robert; Hasholzner, Ralf; Ußmüller, Thomas (Semiconductor Conference Dresden 2011, 2011)
This paper introduces an approach to model the power consumption of analog and mixed-signal systems at system level. The method is based on power state machines and is practically applied to a zero-IF receiver. The power state machines model the static power consumption of components with respect to their current state or state transition. The power consumption per state and state transition, respectively, is obtained from a low-level circuit simulation or from measurement. The concept of power state machines can be used for any analog component and enables the simulation of heterogeneous systems with the benefit of a fast simulation time.
elib2cris::1512001600,glock2011

Eine Aktor-Orientierte Methodik zur Power-Modellierung auf Systemebene - Rosales, Rafael; Klie, Torsten; Glock, Stefan; Xu, Yang; Wang, Bo; Hasholzner, Ralph; Teich, Jürgen; Weigel, Robert (Design & Elektronik, 2012)

Modelling and Simulation of the Energy Efficiency of Heterogeneous Integrated Systems at System Level - Glock, Stefan; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (ITG-Fb. 239: Analog 2013, 2013)
In recent years, the minimization of the power dissipation of integrated heterogeneous systems has become one of the most important design goals. At specification level, at which not all architectural decisions have been taken, exists the highest potential to minimize the power dissipation of the whole system. However, the high complexity of modern het-erogeneous systems complicates the estimation of the power dissipation. Especially the analysis of the power dissipa-tion beyond subsystems is challenging because it necessitates the joint simulation of analogue and digital subsystems. In this context, the question of the right abstraction level for the joint evaluation is demanding because analogue system design follows the bottom-up paradigm, whereas digital system design follows the top-down paradigm. This paper pro-poses a new methodology to model the power dissipation and energy efficiency of complex heterogeneous systems at specification level. The method is based on the hardware description language SystemC. The methodology enables ear-ly power estimation of complete heterogeneous systems. The performance of the modelling approach is shown exem-plarily on an RF-receiver of a mobile radio platform. Those platforms are both battery driven and portable. Therefore, low power consumption is of utmost importance with respect to the later success of the product.
elib2cris::1512001600,glock2013a

Scenario-Based Energy Estimation of Heterogeneous Integrated Systems at System Level - Glock, Stefan; Rosales, Rafael; Reutelhuber, Franz; Glaß, Michael; Teich, Jürgen; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (Proc. 43rd European Microwave Conference, 2013)
One of the most important figures of merit concerning mobile devices is their energy efficiency. However, the modeling of such systems is mainly focused on the functional aspects, but not on the power consumption. Therefore, power estimations can only be accomplished late in the design process, after all architectural decisions have been taken. This might lead to designs that are not optimal with respect to power consumption. To overcome these limitations, this article proposes an efficient and flexible power modeling methodology at system level for heterogeneous integrated systems, allowing to combine state-dependent and environmental dependent power models. In a case study, the energy consumption of an RF transceiver of a mobile phone is estimated in a real-life scenario, including the baseband module, the radio channel, and the base transceiver station in a simulative way. © 2013 European Microwave Association.
elib2cris::1512001600,glock2013b

Semi-Physical Behavioral Modeling of Radio Frequency Power Amplifiers for the Optimization of the Linearity-Efficiency Tradeoff - Glock, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)